Growth and pre-weaning mortality of Katahdin lamb crosses - Mellado, Miguel; Macías, Ulises; Avendaño, Leonel; Mellado, Jesús; García, José Eduardo (Revista Colombiana de Ciencias Pecuarias, 2016)
Katahdin breed sheep is highly disseminated in Mexico. This breed and its crosses have recently gained attention among sheep producers. However, research with crosses between Katahdin and other meat breeds is limited. Objective: to evaluate the genetic and non-genetic factors affecting growth and mortality rate of crossbred lambs from Katahdin ewes fecundated with breeds specialized for meat production. Methods: crossbred lambs (n = 152) from Katahdin ewes sired with Hampshire (KH; n = 43), Texel (KT; n = 53) or Charolais (KCH; n = 56) were evaluated under intensive management conditions. The effects of genotype and non-genetic factors on birth weight, weaning weight, pre-weaning daily weight gain, and mortality rate were determined. Results: breed differences were not detected for birth weight (4 ± 1.1, 4.3 ± 0.9 and 4 ± 1.1 Kg for KCH, KH, KT, respectively), nor for the 60-d weaning weight (20.2 ± 4.3, 20.9 ± 4.3, 18.2 ± 4.2 Kg for KCH, KH, KT, respectively). Weight of lambs did not differ significantly between sexes, but it decreased (p < 0.05) with increased litter size (weaning weight at 60 days for single, twins and triplets was 24.5 ± 2.6, 19.2 ± 3.5, and 14.3 ± 3.8 Kg, respectively). Pre-weaning mortality of KH lambs was 13.3% and it was significantly lower than that of the other genotypes (24.5 and 39.3% for KT and KCH, respectively). Conclusion: inclusion of Charolais, Hampshire or Texel rams in Katahdin flocks results in similar lamb weaning weight, but Hampshire-sired progeny excels regarding pre-weaning survival.